2010
DOI: 10.29043/liminar.v8i2.83
|View full text |Cite
|
Sign up to set email alerts
|

Migraciones y agua en la frontera entre México, Guatemala y Belice: aproximaciones en torno a una relación multiforme

Abstract: La frontera sur de México constituye un escenario de complejos flujos migratorios internos e internacionales. Asimismo, el recurso hídrico se caracteriza por su abundancia debido a fuertes precipitaciones concentradas en pocos meses del año que provocan una presencia multiforme de fuentes de agua superficiales y subterráneas. Este trabajo explora las relaciones entre estas dos realidades que se entrecruzan. A partir de varias definiciones del concepto de frontera, analiza la relación entre las aguas y las dos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The results of this study highlight the heterogeneity in dog populations and dog ownership characteristics across Guatemala, which has likely resulted in under-vaccination of dogs in many rabies endemic communities. Due to the differences that exist in the dog populations in Guatemala, it is necessary to improve local tailored estimates and vaccination coverages, and this is relevant for the regional strategy for rabies elimination in the Americas since Guatemala an Mexico shares 963 km of border [ 39 ], and Mexico was declare free of canine rabies in 2019 [ 40 ]. Interestingly, this study found that dog populations were more strongly correlated with human population density than the total human population in a community; extrapolations based on this density-dependent relationship may offer a more accurate method for apply study data to obtain national and sub-national dog population estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study highlight the heterogeneity in dog populations and dog ownership characteristics across Guatemala, which has likely resulted in under-vaccination of dogs in many rabies endemic communities. Due to the differences that exist in the dog populations in Guatemala, it is necessary to improve local tailored estimates and vaccination coverages, and this is relevant for the regional strategy for rabies elimination in the Americas since Guatemala an Mexico shares 963 km of border [ 39 ], and Mexico was declare free of canine rabies in 2019 [ 40 ]. Interestingly, this study found that dog populations were more strongly correlated with human population density than the total human population in a community; extrapolations based on this density-dependent relationship may offer a more accurate method for apply study data to obtain national and sub-national dog population estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Mexico’s southern border (see Figure 1) is approximately 1,139 kilometers long, of which 962 kilometers border with Guatemala and 176 with Belize. 3 The Suchiate and Usumacinta rivers traverse along half of the border (Kauffer Michel 2010, 32). Simultaneously, 87 percent of the border between Mexico and Belize is demarcated by the Hondo River (García García and Kauffer Michel 2011, 145).…”
Section: Mexico’s Other Southern Border: the Tenosique-petén Borderlandsmentioning
confidence: 99%